2023
DOI: 10.1039/d3md00397c
|View full text |Cite
|
Sign up to set email alerts
|

Current status and prospects of MIL-based MOF materials for biomedicine applications

Zengqin Lin,
Donghui Liao,
Chenyi Jiang
et al.

Abstract: This article mainly reviews the biomedicine applications of two types of metal-organic frameworks (MOFs) of MIL-100(Fe) and MIL-101(Fe). These MOFs have advantages such as high specific surface area, adjustable pore...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 111 publications
0
5
0
Order By: Relevance
“…This approach allows for combination therapy, where different drugs with complementary mechanisms of action can be delivered simultaneously. 103,104 Combination therapy can enhance treatment efficacy, overcome drug resistance, and target multiple pathways involved in cancer progression. 105 MOF-based materials can be engineered to exhibit tunable drug release proles.…”
Section: Cancer Therapy and Drug Deliverymentioning
confidence: 99%
“…This approach allows for combination therapy, where different drugs with complementary mechanisms of action can be delivered simultaneously. 103,104 Combination therapy can enhance treatment efficacy, overcome drug resistance, and target multiple pathways involved in cancer progression. 105 MOF-based materials can be engineered to exhibit tunable drug release proles.…”
Section: Cancer Therapy and Drug Deliverymentioning
confidence: 99%
“…The responsive disintegration of the MOF structure requires the stimulation of external factors, and TME is an internal environmental network with extremely complex components. It has been reported that a slightly acidic pH value, overexpressed glutathione (GSH), hydrogen peroxide (H 2 O 2 ), and other substances in the TME can destroy the coordination bonds in the structure of MOFs and stimulate their disintegration. If an iron-containing MOF is loaded with chemotherapeutic agents, the responsive disintegration of the MOF in the TME can release chemotherapeutic agents and Fe 3+ ions. Chemotherapy drugs can kill tumor cells through specific biological processes and mechanisms, and Fe 3+ can induce ferroptosis of tumor cells through the clearance of GSH and the generation of Fe 2+ to achieve the treatment of tumor cells.…”
Section: Introductionmentioning
confidence: 99%
“… 43 46 If an iron-containing MOF is loaded with chemotherapeutic agents, the responsive disintegration of the MOF in the TME can release chemotherapeutic agents and Fe 3+ ions. 47 49 Chemotherapy drugs can kill tumor cells through specific biological processes and mechanisms, and Fe 3+ can induce ferroptosis of tumor cells through the clearance of GSH and the generation of Fe 2+ to achieve the treatment of tumor cells.…”
Section: Introductionmentioning
confidence: 99%
“…Their large surface area, amphiphilic internal microenvironment and their possible functionalization make these materials suitable to host a large variety of drugs with excellent loading capacities. 7–14 Their high chemical and structural diversity can confer to these nanocarriers valuable features such as progressive and eventually stimuli-responsive drug release properties as well as complementary functionalities of interest for diagnosis and imaging. 15–21 Note that MOFs have been mainly explored to date for cancer therapy and their performance in therapies of inflammatory diseases such as RA has only recently been reported.…”
Section: Introductionmentioning
confidence: 99%